2017
DOI: 10.1038/s41467-017-01909-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cortical network connectivity with long-term brain-machine interface exposure after chronic amputation

Abstract: Studies on neural plasticity associated with brain–machine interface (BMI) exposure have primarily documented changes in single neuron activity, and largely in intact subjects. Here, we demonstrate significant changes in ensemble-level functional connectivity among primary motor cortical (MI) neurons of chronically amputated monkeys exposed to control a multiple-degree-of-freedom robot arm. A multi-electrode array was implanted in M1 contralateral or ipsilateral to the amputation in three animals. Two clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Recent studies have revealed that BMI training in a closed-loop condition improves BMI performance. It has been demonstrated that closed-loop training improves the control of a neuroprosthetic device using multi-unit activities in accordance with some network plasticity and reorganization (Orsborn et al, 2014 ; Balasubramanian et al, 2017 ). Similarly, the performance of non-invasive BMI can be predicted by cortical activities and improved by closed-loop neurofeedback training (Hwang et al, 2009 ; Blankertz et al, 2010 ; Sugata et al, 2016 ; Wan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that BMI training in a closed-loop condition improves BMI performance. It has been demonstrated that closed-loop training improves the control of a neuroprosthetic device using multi-unit activities in accordance with some network plasticity and reorganization (Orsborn et al, 2014 ; Balasubramanian et al, 2017 ). Similarly, the performance of non-invasive BMI can be predicted by cortical activities and improved by closed-loop neurofeedback training (Hwang et al, 2009 ; Blankertz et al, 2010 ; Sugata et al, 2016 ; Wan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore compared effective connectivity among both BCI and non-BCI units during joystick trials and during BCI trials. We evaluated pairwise effective connectivity among all BCI units ( Table 1 , top row, left number) and all non-BCI units that were modulated significantly during both joystick and BCI trials ( Table 1 , other rows, right number in each cell) using Granger causality adapted for point process models ( Kim et al, 2011 ; Balasubramanian et al, 2017 ), as described in Materials and Methods. Figure 8 shows the Granger connectivity matrices from an example session, computed using equal numbers of joystick ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that effective connectivity among the M1 BCI units controlling a reach-to-grasp robot changes progressively as non-human primates acquired proficient control, although the time course of these changes differed depending on whether the M1 BCI population was contralateral or ipsilateral to an upper extremity amputation ( Balasubramanian et al, 2017 ). Here, we found that effective connectivity increased during BCI as compared with joystick control in one monkey but not the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetric stability likely reflects 1) flexibility in the activity of individual neurons within the intrinsic manifold or 2) constraints imposed by the intrinsic manifold on behavioral improvement (and changes in neural connectivity) possible within a training session. Note that the density of functional network connections increased monotonically in monkey Z; the existing network connections were first pruned before comparably denser connectivity emerged in monkey K (Balasubramanian et al 2017). Monkey K was forced to alter an existing intrinsic manifold of which the neurons were arbitrarily assigned for reaching and grasping.…”
mentioning
confidence: 99%